THE PREVENTION OF PULMONARY EMBOLISM FOLLOWING ENDOVENOUS LASER COAGULATION OF VARICOSE VEINS OF THE LOWER LIMBS - R. A. Akhadov; A. B. Sazonov; K. V. Kitachev; V. V. Sizenko; G. G. Khubulava (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of the research was to compare the influence of the endovenous laser coagulation (EVLC) on the pulmonary system with the performing of the Troyanov–Trendelenburg operation and without it. MATERIAL AND METHODS. We performed 108 endovenous laser coagulation for 16 patients without great saphenous vein trunk dressing and for 92 patients with dressing. The Russian portable laser device «Diolan» was used for the endovenous laser coagulation, wavelength of 980 nm, capacity of 16–20 watts. An intraoperative transesophageal echocardiography was carried to 12 patients to visualize heart chambers in the moment of the laser exposure. RESULTS. The patients without Troyanov–Trendelenburg operation had massive inflow of gas bubbles and detritus into pulmonary system during the endovenous laser coagulation. CONCLUSION. The obtained results showed the qualitative and quantitative differences in the character of the substrate entering the heart and the pulmonary system.